2020
DOI: 10.1101/2020.01.13.905034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic effects on educational attainment in Hungary

Abstract: Educational attainment is a substantially heritable trait, and it has recently been linked to specific genetic variants by genome-wide association studies (GWASs). However, some variants may index social stratification, and polygenic score (PGS) heritability may differ across cohorts reflecting the changing relative influence of genetic and environmental influences on educational attainment over time. We used a Hungarian (N=829) sample of healthy volunteers to assess the validity of the most recent educational… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Looking toward a broader social context, several insightful studies have shown that the heritability of educational attainment increases with equality of opportunity. We see evidence for this within countries over time (Heath et al, 1985), within and between countries over time (Engzell & Tropf, 2019; de Zeeuw, de Geus, & Boomsma, 2015), and within countries following a major policy change (Colodro-Conde, Rijsdijk, Tornero-Gómez, Sánchez-Romera, & Ordoñana, 2015; Rimfeld et al, 2018; Ujma et al, 2022). Although there is also some evidence going in the other direction (Silventoinen et al, 2020), the overall pattern appears to be that diffusion of educational opportunity results in genes explaining a relatively greater proportion of variance in educational attainment.…”
Section: Interpreting Heritabilitymentioning
confidence: 84%
“…Looking toward a broader social context, several insightful studies have shown that the heritability of educational attainment increases with equality of opportunity. We see evidence for this within countries over time (Heath et al, 1985), within and between countries over time (Engzell & Tropf, 2019; de Zeeuw, de Geus, & Boomsma, 2015), and within countries following a major policy change (Colodro-Conde, Rijsdijk, Tornero-Gómez, Sánchez-Romera, & Ordoñana, 2015; Rimfeld et al, 2018; Ujma et al, 2022). Although there is also some evidence going in the other direction (Silventoinen et al, 2020), the overall pattern appears to be that diffusion of educational opportunity results in genes explaining a relatively greater proportion of variance in educational attainment.…”
Section: Interpreting Heritabilitymentioning
confidence: 84%